Singing Games - Jane Beethoven; Rosanne Emery; Synía Carroll-McQuillan.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1995)
Viewers learn games that include music and movement - - See how children from other countries play singing games - - Respond to the rhythms of singing games - - Play along with a game from Africa.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - About Singing Games - - Episode 1: Here Comes Valerie (United States) - - Episode 2: La Vibora (Mexico) - - Episode 3: Juggling Game (Japan) - - Episode 4: Che Che Koolay (Ghana) - - Correlations with THE MUSIC CONNECTION - - About the Artists.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Singing games